2017
DOI: 10.1089/acm.2017.0098
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of GuiZhi-ShaoYao-ZhiMu Decoction for Treating Rheumatoid Arthritis: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: The Traditional Chinese Medicine, GSZD, may have equal or superior effectiveness and safety for treating RA compared to Western RA drugs. It should be considered a viable alternative to Western medicine. However, more long-term research is needed in larger patient groups to better establish its safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…Additionally, after 12 to 24 weeks of treatment with Tripterygium wilfordii Hook.f in combination with methotrexate, there was an improvement in the level of CRP (Lv et al, 2015). Furthermore, several randomized controlled trial about the efficacy of Gui-Zhi-Shao-Yao-Zhi-Mu-Tang with WM showed that after taking Gui-Zhi-Shao-Yao-Zhi-Mu-Tang with WM for 4-12 weeks, there was a significant decrease in ESR, RA factor, and CRP (Daily et al, 2017). The Pathological mechanisms of RA are characterized by chronic systemic inflammation, and patients using CHP for 30-180 days may achieve an improved antiinflammatory effect in terms of reducing their risk of IS.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Additionally, after 12 to 24 weeks of treatment with Tripterygium wilfordii Hook.f in combination with methotrexate, there was an improvement in the level of CRP (Lv et al, 2015). Furthermore, several randomized controlled trial about the efficacy of Gui-Zhi-Shao-Yao-Zhi-Mu-Tang with WM showed that after taking Gui-Zhi-Shao-Yao-Zhi-Mu-Tang with WM for 4-12 weeks, there was a significant decrease in ESR, RA factor, and CRP (Daily et al, 2017). The Pathological mechanisms of RA are characterized by chronic systemic inflammation, and patients using CHP for 30-180 days may achieve an improved antiinflammatory effect in terms of reducing their risk of IS.…”
Section: Discussionmentioning
confidence: 98%
“…We observed an association between using CHP in combination with WM and a lower risk of IS among patients with RA (aHR for IS: 0.67 vs. non-CHP group). A possible reason for this is that the commonly used CHP, such as Gui-Zhi-Shao-Yao-Zhi-Mu-Tang, alleviate systemic inflammation by lowering the CRP, and erythrocyte sedimentation rate (ESR), which may decrease the progression of atherosclerosis, the main pathologic process of IS (Daily et al, 2017). Another commonly prescribed single herb, Spatholobus suberectus Dunn (Ji-Xie-Teng), has also been shown to suppress inflammation by decreasing TNF-a secretion .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations